2000
DOI: 10.1063/1.1290275
|View full text |Cite
|
Sign up to set email alerts
|

Hole blocking in carbon nanotube–polymer composite organic light-emitting diodes based on poly (m-phenylene vinylene-co-2, 5-dioctoxy-p-phenylene vinylene)

Abstract: In order to investigate the role of carbon nanotubes in a polymer matrix, organic light-emitting diodes were fabricated from a polymer composite composed of poly (m-phenylene vinylene-co-2,5-dioctoxy-p-phenylene) (PmPV) and dispersed single-wall carbon nanotubes (SWNTs). Tris-(8-hydroxyquinolinolato) aluminum (Alq3) doped by Nile Red was used as an emissive material between the polymer composite and cathode. The device fabricated without SWNTs dispersed in the PmPV shows a dominant emission near red at 600 nm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 12 publications
5
62
0
Order By: Relevance
“…Therefore, the mechanism for the formation of the excited state in the polymer involves the ruthenium complex in a stepwise electron transfer process. In the case of the PDPV-ZnO:Mg composite the band gap of ZnO is higher than that of the polymer and the latter mechanism of the electric-field switching between blue-green and red emissions does not work (as well as the mechanism proposed for the emission from PPV-carbon nanotube composite ( Woo et al, 2000). Fig.…”
Section: Switching Of Cathodoluminescence From Zno Nanoparticle/polymmentioning
confidence: 99%
“…Therefore, the mechanism for the formation of the excited state in the polymer involves the ruthenium complex in a stepwise electron transfer process. In the case of the PDPV-ZnO:Mg composite the band gap of ZnO is higher than that of the polymer and the latter mechanism of the electric-field switching between blue-green and red emissions does not work (as well as the mechanism proposed for the emission from PPV-carbon nanotube composite ( Woo et al, 2000). Fig.…”
Section: Switching Of Cathodoluminescence From Zno Nanoparticle/polymmentioning
confidence: 99%
“…The buffer layer leads to a reduction of the charge injection barrier and an even charge distribution with a large contact area at the electrodes/organics interface. A recent work shows that the dispersion of SWNTs in a host polymer (PmPV, hole conducting) traps the holes in a double emitting organic light emitting diode (DE-OLED) [63]. The device fabricated without SWNTs dispersed in the PmPV has shown a dominant emission near red at 600 nm, which is in the range of the characteristic emission of Nile Red-doped Alq3, while the addition of a www.intechopen.com small amount of SWNTs enhances a green emission, In addition, the devices fabricated with the polymer/SWNTs composite have shown an increase in the oscillator strength of the green emission with a dominant emission peak near 500 nm, the characteristic emission of PmPV.…”
Section: Optical Limiting Devicesmentioning
confidence: 99%
“…For biosensor applications, it has been demonstrated that the CPs/CNTs nanocomposites are very attractive as tranducers because they provide the best electron transfer and assure a faster www.intechopen.com ion mass transfer [28]. In some host polymers, the CNTs additive has found to act as a holeblocking causing a shift of the recombination emission [29,63]. The interaction between host polymer and CNTs additive is considered to be the main reason accounting for all of these modifications.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent electrical properties of CNs make them attractive candidates for new electronic devices. [8][9][10] Research [11][12][13][14][15] into the mechanical properties of CN composites has revealed that CNs can be potentially used as reinforcement fillers in polymer composite systems.…”
Section: Introductionmentioning
confidence: 99%
“…As hard conductive materials, LCE-CN composites show great potential for use as antistatic coatings or for electromagnetic shielding for electronic devices. [20][21][22][23] CNs offer an alternative for polymer matrix reinforcement [20][21][22] and enhance the electronic properties [8][9][10] of the resulting composite. Although many studies have sought to improve the mechanical performance of polymer-CN composites, they provide only limited information concerning the surface modification of CNs.…”
Section: Introductionmentioning
confidence: 99%